A Clinical Retrospective Study of Recurrent Painful Ophthalmoplegic Neuropathy in Adults - Cheng Li; Xinyi Huang; Xiao Tan; Yannan Fang; Jianhua Yan (Journal of Ophthalmology)
Introduction. Recurrent painful ophthalmoplegic neuropathy (RPON) is quite rare and usually occurs in children. In this report, we describe the clinical features, diagnosis, and treatment of RPON in adults. Methods. A retrospective review was conducted of all RPON cases seen and treated at the Zhongshan Ophthalmic Center of Sun Yat-sen University and the Department of Neurology of the First Affiliated Hospital, Sun Yat-sen University, Guangzhou, China, over the period from January 2016 to May 2020. Results. A total of 8 patients (3 males and 5 females) with a mean age of 42.9 years (range: 23–64 years) met the diagnostic criteria of RPON. Headaches were present prior to the onset of ophthalmoplegic neuropathy in 50% of these patients, while in the remaining 50%, headaches occurred simultaneously with eye symptoms. The degree of these headaches was described as being mild or moderate. Abnormalities involving cranial nerve III were the most frequently reported pathologies (6 cases, 75%), followed by nerve VI (4 cases, 50%) and then nerve IV (1 case, 12.5%) (more than one nerve was affected in some cases). Following either with glucocorticoid treatment or with observation only, symptoms and signs within all 8 patients completely dissipated within 3–28 days. Conclusions. All adult cases of RPON along with their clinical features as reported here were similar to those of children.